Debate-of-ideas setting and configurations of play among beginner female students - Zerai, Zeineb; Mnedla, Sofien (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
The current study aimed to investigate the concept of game model and the notion of prototypical configuration, which are designed and used to conduct qualitative analysis of game-play in team sports. To carry out this study, a qualitative methodology was used, and a sample of 20 female students (aged 19± 0.3 years) was taken from the Physical Education program at Sohar University. Data were collected through video recordings. The main result showed a noteworthy progression at the level of the tactics of the game which is translated by the elaboration of the new configuration of play in the game. This evolutionary process of configurations emphasizes a progressive understanding of the game based on critical thinking. These configurations are momentary and over the course of the game, they are linked to each other. Nevertheless, to decode them, reference points are needed, operative images which, after identification, allow for a quicker response adapted to the perceived situation. A proper analysis of player thinking behind the different forms of play, moves and configurations of play requires that one assumes the development of a tactical intelligence of game play.